Analisis ketersediaan dan kebutuhan air untuk Daerah Irigasi Pitap - Refky Husada Aditama; Adriani Muhlis (P3M Politeknik Negeri Banjarmasin, 2019)
Agriculture is a field that plays a very important role in meeting the food needs of a country. Irrigation is aimed at controlling or controlling water on land, so that the farming process is more productive and effective. One area that has the potential to be developed is Balangan Regency, South Kalimantan. Therefore made Pitap irrigation channels. The construction of the irrigation channel has been around for more than 6 years (until 2019), it is necessary to observe and analyze the water demand and the availability of water in the irrigation in order to create a suitable development planning and productivity of agricultural products for the area. This study uses primary and secondary data collection methods, and the results obtained in the form: Water demand in November is 5.45 m3 / second for the first half, and for the second half is 5.72 m3 / second, water availability in November is 3,981 m3 / second (taken from the mainstay of 80% monthly discharge), the water balance shows that in November there was a water shortage deficit of 1.47 m3 / second for the first half, and 1.74 m3 / second.